WILDFIRE AS A HYDROLOGICAL AND GEOMORPHOLOGICAL AGENT - Shakesby R.A.; Doerr S.H. (My University, 2006)
Wildfire can lead to considerable hydrological and geomorphological change, both directly by weathering bedrock surfaces and changing soil structure and properties, and indirectly through the effects of changes to the soil and vegetation on hydrological and geomorphological processes. This review summarizes current knowledge and identifies research gaps focusing particularly on the contribution of research from the Mediterranean Basin, Australia and South Africa over the last two decades or so to the state of knowledge mostly built on research carried out in the USA. Wildfire-induced weathering rates have been reported to be high relative to other weathering processes in fire-prone terrain, possibly as much as one or two magnitudes higher than frost action, with important implications for cosmogenic-isotope dating of the length of rock exposure. Wildfire impacts on soil properties have been a major focus of interest over the last two decades. Fire usually reduces soil aggregate stability and can induce, enhance or destroy soil water repellency depending on the temperature reached and its duration. These changes have implications for infiltration, overland flow and rainsplash detachment. A large proportion of publications concerned with fire impacts have focused on post-fire soil erosion by water, particularly at small scales. These have shown elevated, sometimes extremely large post-fire losses before geomorphological stability is re-established. Soil losses per unit area are generally negatively related to measurement scale reflecting increased opportunities for sediment storage at larger scales. Over the last 20 years, there has been much improvement in the understanding of the forms, causes and timing of debris flow and landslide activity on burnt terrain. Advances in previously largely unreported processes (e.g. bio-transfer of sediment and wind erosion) have also been made. Post-fire hydrological effects have generally also been studied at small rather than large scales, with soil water repellency effects on infiltration and overland flow being a particular focus. At catchment scales, post-fire accentuated peakflow has received more attention than changes in total flow, reflecting easier measurement and the greater hazard posed by the former. Post-fire changes to stream channels occur over both short and long terms with complex feedback mechanisms, though research to date has been limited. Research gaps identified include the need to: (1) develop a fire severity index relevant to soil changes rather than to degree of biomass destruction; (2) isolate the hydrological and geomorphological impacts of fire-induced soil water repellency changes from other important post-fire changes (e.g. litter and vegetation destruction); (3) improve knowledge of the hydrological and geomorphological impacts of wildfire in a wider range of fire-prone terrain types; (4) solve important problems in the determination and analysis of hillslope and catchment sediment yields including poor knowledge about soil losses other than at small spatial and short temporal scales, the lack of a clear measure of the degradational significance of post-fire soil losses, and confusion arising from errors in and lack of scale context for many quoted post-fire soil erosion rates; and (5) increase the research effort into past and potential future hydrological and geomorphological changes resulting from wildfire. © 2005 Elsevier B.V. All rights reserved.
Keywords: FOREST FIRE; GLOBAL WARMING; INFILTRATION; MASS MOVEMENT PROCESSES; PALAEOFIRE; PEAKFLOW; ROCK WEATHERING; SEDIMENT YIELD; SOIL EROSION; SOIL HYDROPHOBICITY; TOTAL FLOW; WILDFIRE